Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Perilaku Konsumtif pada Siswa SMK Teladan Tanah Jawa: The Influence of Financial Literacy and Lifestyle on Consumptive Behavior of SMK Teladan Tanah Jawa Students - Gultom, Binsar Tison; Silalahi, Define Rohito (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to: 1. To determine the effect of financial literacy on consumer behavior in SMK Teladan Tanah Jawa students. 2. To determine the effect of lifestyle on consumer behavior in SMK Teladan Tanah Jawa students. 3. To determine the effect of financial literacy and lifestyle on consumer behavior in SMK Teladan Tanah Jawa students. The population in this study were all students of SMK Teladan Tanah Jawa. The sampling technique used in this study was simple random sampling with 92 respondents. Data collection techniques were in the form of observation, questionnaires, and documentation. This study is quantitative. The study's results stated that: 1) Financial literacy significantly affects consumer behavior in SMK Teladan Tanah Jawa students by 0.377. 2) Lifestyle positively and significantly affects consumer behavior in SMK Teladan Tanah Jawa students by 0.472. 3) Financial Literacy and Lifestyle significantly and jointly affect consumer behavior. This result can be seen in the F test where the F count value is 17.459 > ??from the F table with df = n-k-1 (92-2-1) of 2.36. The R Square determination coefficient test is known to be 0.282, which means 28.2% of financial literacy and lifestyle on student wasteful behavior, and 71.8% is the influence of other variables not examined in this study.